Kewenangan Pemegang Protokol Notaris yang Meninggal Dunia untuk Mengeluarkan Salinan Akta dari Minuta Akta yang Belum Lengkap Tanda Tangannya - Anggri Rudianto; Suhariningsih Suhariningsih; Bambang Winarno (Faculty of Law, Universitas Pekalongan, 2020)
This legal research is a study of normative law with the approach of legislation, conceptual and case. The purpose of this research is to know and analyze the existence of legal vacuum because not yet the regulation of notary protocol holder authority related to minuta deed which not yet complete its signature and responsibility of protocol holder if still issuing copy of related deed. The provisions of Article 62 of the UUJNP concerning the reasons for the handover of a notary protocol are attributed to one of the process of making notarial deeds as stipulated in Article 16 paragraph (1) subparagraph m UUJNP and having the authority to grant grosse, copy and quotation of deed Article 64 UUJN as well as holders of notary protocol also has the authority as the notary itself. Based on the description, it is possible that the notary who passed away has not completed the signature that must be in the minuta so that the authority of the protocol holders related to the deed becomes a separate issue. The responsibility of the protocol holders against the notarized deed minas is to make copies of the original letters under the hand in the form of copies containing the description as written and described in the corresponding letter (Article 15 paragraph (2) letter c UUJNP) and not authorized issuing a copy of the deed because the minus deed is not an authentic deed but a deed under the hand. Judicial implication for the notary protocol holder issuing a copy of the deed minus not noted by a notary public is the holder of notary protocol may be subject to criminal sanction namely Article 55 juncto Article 264 of the criminal code is making a fake authentic act deliberately.Keywords:Notaries; Notary Protocols; Notary Protocol Holders.